Sikap Ilmiah Mahasiswa Teknik Elektro pada Mata Kuliah Dasar Elektronika - Hermin Arista; Ary Analisa Rahma (Journal on Education, 2023)
This study used a qualitative approach with a descriptive research method. This study aims to describe the scientific attitude of electrical engineering students in the Basic Electronics subject at the Faculty of Engineering, University of Panca Marga Probolinggo in the third semester of the 2022/2023 academic year. The sample in this study was 40 students. In this study, the data was obtained by observing students in teaching and learning activities in the classroom directly. The indicators of the observation are curiosity, discovery and creativity, working in groups, critical thinking, and respect for facts/data. According to the results of this research, data obtained from each aspect namely, the highest average value of students' scientific attitude was cooperation attitude in 81.7% (very good category). The second was respect for facts/data in 79% (good category). Furthermore, the attitude of curiosity was the third in 74.3% (good category). The fourth was the attitude of discovery and creativity in 71.7% (good category). The attitude of critical thinking was in the fifth and the lowest average value of scientific attitude in 67.7% (enough category). The average percentage of students' scientific attitude analysis is 74.9% in the good category. So, it stated that the scientific attitude of electrical engineering students in the Basic Electronics subject at the Faculty of Engineering, University of Panca Marga Probolinggo in the third semester of the 2022/2023 academic year was quite good.